2012
DOI: 10.1002/jbmr.1604
|View full text |Cite
|
Sign up to set email alerts
|

miR-182 is a negative regulator of osteoblast proliferation, differentiation, and skeletogenesis through targeting FoxO1

Abstract: Uncontrolled oxidative stress impairs bone formation and induces age-related bone loss in humans. The FoxO family is widely accepted to play an important role in protecting diverse cells from reactive oxygen species (ROS). Activation of FoxO1, the main FoxO in bone, stimulates proliferation and differentiation as well as inhibits apoptosis of osteoblast lineage cells. Despite the important role of FoxO1, little is known about how FoxO1 expression in bone is regulated. Meanwhile, several recent studies reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
126
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(132 citation statements)
references
References 40 publications
5
126
0
1
Order By: Relevance
“…**p < 0.01. such as MIR182, may be responsible for regulating the FOXO1 protein level when an increase in FOXO1 mRNA is observed. 57,58 MicroRNAs bind to the 3'UTR of the mRNA of specific genes and suppress their translation, 59 thus preventing changes in protein expression despite changes in the mRNA level. Future studies should investigate whether microRNAs are involved in the regulation of FOXO1 translation.…”
Section: Discussionmentioning
confidence: 99%
“…**p < 0.01. such as MIR182, may be responsible for regulating the FOXO1 protein level when an increase in FOXO1 mRNA is observed. 57,58 MicroRNAs bind to the 3'UTR of the mRNA of specific genes and suppress their translation, 59 thus preventing changes in protein expression despite changes in the mRNA level. Future studies should investigate whether microRNAs are involved in the regulation of FOXO1 translation.…”
Section: Discussionmentioning
confidence: 99%
“…51 In particular, several recent studies revealed that FoxO1 is able to promote osteoblast differentiation of the progenitor cells. 20,21,[52][53][54] However, its role in regulating osteogenic differentiation of ADSCs has not been reported yet. The data obtained from the present Western blot analysis showed that in human ADSCs, expression of FoxO1 was upregulated after addition of the osteogenic medium, and more importantly, cotreatment of fullerol with the osteogenic medium further augmented expression of this transcript factor and its significant targets Runx2, OCN, and SOD2 ( Figure 5).…”
mentioning
confidence: 99%
“…In addition, microRNAs (miRNAs) regulate gene expression at the post-transcriptional level and were recently shown to move between cells via gap junctions [28,29]; therefore, these small regulatory RNAs may be transported across gap junctions from MLO-A5 cells to 10T-GFP cells. The actions of miRNAs are the subject of increasing attention in a variety of fields [30][31][32]; in a recent study, overexpression of miR218 increased the expression 224 MIKAMI ET AL.…”
Section: Discussionmentioning
confidence: 99%